Three-Dimensional Printing in Spinal Surgery - Araújo Júnior, Francisco Alves de; Ribas Filho, Jurandir M.; Malafaia, Osvaldo; Arantes, Aluízio Augusto; Ceccato, Guilherme Henrique Weiler; Santos Neto, Pedro Helo dos (World neurosurgery, 2024)
Carry out an update and systematic review on the use of three-dimensional printing (3DP) in spinal surgery. A systematic literature review was performed using the PubMed database in March 2024. “Spine surgery” and “3DP” were the search terms. Only articles published from 2014 to 2024 and clinical trails were selected for inclusion. Non-English or Spanish articles were excluded. This review complied with the Preferred Reported Items for Systematic Reviews and Meta-Analysis guideline. Ten articles were included after screening and evaluation. The majority of the studied diseases were deformities (n = 3) and traumas (n = 3), followed by degenerative diseases (n = 2). Two articles dealt with surgical techniques. Six articles studied the creation of personalized guides for inserting screws; 2 were about education, one related to educating patients about their disease and the other to teaching residents surgical techniques; 2 other articles addressed surgical planning, where biomodels were printed to study anatomy and surgical programming. 3DP is one of the most-used tools in spine surgeries, but there are still randomized articles available on the subject. Using this technology seems to have a positive effect on patient education regarding their disease and surgical planning.